2017
DOI: 10.1155/2017/7652313
|View full text |Cite
|
Sign up to set email alerts
|

Size Effect of Concrete Specimens on the Acoustic Emission Characteristics under Uniaxial Compression Conditions

Abstract: Acoustic emission (AE) experiments under uniaxial compression and cyclic loading-unloading compression conditions were performed using different sizes of cubic concrete specimens. The influences of the loading methods and the concrete sizes on the mechanical parameters and the concrete AE activities were analyzed. The loading method was found to have great impact on the deformation, failure, and energy dissipation of concrete materials. With the increase of the material size, the uniaxial compressive strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
(23 reference statements)
1
6
0
Order By: Relevance
“…Along the same lines, it has been shown that the energy release rate, as it is recorded by the AEs technique, obeys a power law at the stage of intense internal damage [ 45 ]. Similar observations are reported for the cumulative AE rings, the evolution of which, at loading levels close to those causing fracture, is dictated by a strongly non-linear law [ 46 ].…”
Section: Introductionsupporting
confidence: 80%
“…Along the same lines, it has been shown that the energy release rate, as it is recorded by the AEs technique, obeys a power law at the stage of intense internal damage [ 45 ]. Similar observations are reported for the cumulative AE rings, the evolution of which, at loading levels close to those causing fracture, is dictated by a strongly non-linear law [ 46 ].…”
Section: Introductionsupporting
confidence: 80%
“…The calculated b value is usually divided into three types: stress level, number of AEs, and crack propagation stage. For the comparative analysis, the value of b in this section is the level of relative stress increase per 0.1. As can be seen from Figure , the b value exhibits a rising, fluctuating, and continuously decreasing variation law in the three types of concrete compression processes, but the magnitude of the b value and the range of the fluctuations are significantly different.…”
Section: Results and Discussion Of Test Resultsmentioning
confidence: 99%
“…Crack initiation strength and crack damage are critical to distinguishing between crack initiation and unsteady propagation. Therefore, the AE signal variation characteristics can accurately reflect the crack initiation and propagation law of concrete, the same as the moving point regression method and the stress–strain curve observation method. , Crack initiation strength and crack damage stress are critical to distinguish between crack initiation and unsteady propagation. Tensile cracks are the dominant crack morphology.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reveal the influence of grouting on the mechanical characteristics of fractured rock, domestic and foreign scholars have conducted a lot of research on it through indoor tests and numerical simulation [7,8] and further studied the mechanism of grouting reinforcement on this basis [9][10][11][12][13]. Yang [14] studied the structure of randomly fractured rock mass, the law of grouting permeability, the characteristics of randomness and anisotropy, and the stability of grouting reinforcement.…”
Section: Introductionmentioning
confidence: 99%